Correction: COVID-19 stressors and mental health problems amongst women who arrived as refugees and those born in Australia. - Susan J Rees; Mohammed Mohsin; Alvin Kuowei Tay; Batool Moussa; Louis Klein; Nawal Nadar; Fatima Hussain; Yalini Krishna; Batoul Khalil; Mariam Yousif; Derrick Silove; Jane Fisher (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0002073.].